Identification of mechanisms for financing of energy efficiency and renewable energy initiatives to increase investment in the Commonwealth of Dominica - NU. CEPAL. Sede Subregional para el Caribe (ECLAC, 2016)
This document identifies mechanisms for financing investments in energy efficiency and renewable energy initiatives in the Commonwealth of Dominica. The overall objective of this study is to examine financing opportunities which will provide greater incentives for the development of energy efficiency measures and implementation of renewable energy technologies.